The inflammation‐based modified Glasgow prognostic score is associated with survival in stable heart failure patients. (25th February 2020) - Cho, Anna; Arfsten, Henrike; Goliasch, Georg; Bartko, Philipp E.; Wurm, Raphael; Strunk, Guido; Hülsmann, Martin; Pavo, Noemi
Abstract: Aims: The progression of heart failure is presumably dependent on the individual inflammatory host response. The combination of the inflammatory markers, albumin, and C‐reactive protein, termed modified Glasgow prognostic score (mGPS), has been derived from cancer patients and validated in multiple cohorts. This study aimed to investigate the impact of the easily available mGPS on survival of stable patients with heart failure with reduced ejection fraction (HFrEF). Methods and results: Patients with stable HFrEF undergoing routine ambulatory care between January 2011 and November 2017 have been identified from a prospective registry at the Medical University of Vienna. Comorbidities, laboratory data as well as the nutritional risk index at baseline were assessed. All‐cause mortality was defined as the primary study end point. The mGPS was calculated, and its association with heart failure severity and impact on overall survival were determined. Data were analysed for a total of 443 patients. The mGPS was 0 for 352 (80%), 1 for 76 (17%), and 2 for 14 (3%) patients, respectively. Elevation of mGPS was associated with worsening of routine laboratory parameters linked to prognosis, especially NT‐proBNP [median 1830 pg/mL (IQR 764–3455) vs. 4484 pg/mL (IQR 1565–8003) vs. 6343 pg/mL (IQR 3750–15401) for mGPS 0, 1, and 2, respectively; P < 0.001] and nutritional risk index. In the Cox regression analysis, the increase of mGPS was associated with adverse outcome in the univariate analysis [crude hazard ratio 3.00 (95% CI 2.14–4.21), P < 0.001] and after adjustment for multiple covariates as age, gender, body mass index, and glomerular filtration rate as well as heart failure severity reflected by NT‐proBNP and New York Heart Association class [adj. hazard ratio 1.87 (95% CI 1.19–2.93), P = 0.006]. Conclusions: Enhanced inflammation and nutritional depletion are more common in advanced heart failure. The inflammation‐based score mGPS predicts survival in HFrEF patients independently of NT‐proBNP emphasizing the significance of the individual pro‐inflammatory response on prognosis.